Karakteristik dan Kepatuhan Unit Penangkapan Ikan Pukat Labuh di Tanjungbalai Asahan - Benardo Nababan; Roma Yuli Hutapea (Politeknik Kelautan dan Perikanan Sorong, Indonesia, 2021)
The study of long bag set nets in Tanjungbalai aims to determine the characteristics and level of compliance with applicable regulations. The study of characteristics was carried out by following fishing operation at sea in 2018, while compliance was analyzed from the supervision data of the Asahan PSDKP Unit in 2019 and 2020. The long bag set net in Tanjungbalai Asahan is classified as a trap. The long bag set nets are installed permanently in the waters for a certain period of time, utilizing the tidal currents of the waters, and using 2 (two) large anchor units as a barrier so that the nets are not carried away by the current. The main catch is anchovy, while the by-catch are squid, gulama, pomfret and layur. The compliances of the long bag set nets is reviewed from 6 (six) aspects:(1) completeness of the fishing license (SIPI), (2) conformity of fishing gear specifications, (3) suitability of fishing grounds, (4) suitability of fishing base, (5) completeness of legal operational letter (SLO), and (6) port clearance (SPB). The compliance of the long bag set netm fishermen in Tanjungbalai Asahan is very good because they have followed all applicable regulations.